Implementation of Video Visits During COVID-19: Lessons Learned From a Primary Care Practice in New York City - Sinha, Sanjai; Kern, Lisa M.; Gingras, Laura F.; Reshetnyak, Evgeniya; Tung, Judy; Pelzman, Fred; McGrath, Thomas A.; Sterling, Madeline R. (Frontiers in Public Health, 2020)
Abstract: Background: During the height of the coronavirus (COVID-19) pandemic, there was an unprecedented demand for “virtual visits,” or ambulatory visits conducted via video interface, in order to decrease the risk of transmission. Objective: To describe the implementation and evaluation of a video visit program at a large, academic primary care practice in New York, NY, the epicenter of the COVID-19 pandemic. Design and Participants: We included consecutive adults (age >18) scheduled for video visits from March 16, 2020 to April 17, 2020 for COVID-19 and non-COVID-19 related complaints. Intervention: New processes were established to prepare the practice and patients for video visits. Video visits were conducted by attendings, residents, and nurse practitioners. Main Measures: Guided by the RE-AIM Framework, we evaluated the Reach, Effectiveness, Adoption, and Implementation of video visits. Key Results: In the 4 weeks prior to the study period, 12 video visits were completed. During the five-week study period, we completed a total of 1,030 video visits for 817 unique patients. Of the video visits completed, 42% were for COVID-19 related symptoms, and the remainder were for other acute or chronic conditions. Video visits were completed more often among younger adults, women, and those with commercial insurance, compared to those who completed in-person visits pre-COVID (all p<0.0001). Patients who completed video visits reported high satisfaction (mean 4.6 on a 5-point scale [SD: 0.97]); 13.3% reported technical challenges during video visits. Conclusions: Video visits are feasible for the delivery of primary care for patients during the COVID-19 pandemic.